EVALUATING PAVEMENT SURFACE CONDITION FOR URBAN NETWORK USING MICRO PAVER AND ArcGIS SOFTWARE - ABDULMAJEED, ABDULSALAM ISLAM; ALASWADKO, NAHLA HUSSEIN (Journal of Duhok University, 2023)
Pavement is one of the fundamental components of the road system and its management is a major issue for organization and pavement engineers in the highway sector. To identify the required maintenance and repair works and to keep it at an acceptable level of serviceability, a vital indicator to evaluate the pavement condition of roadways is the pavement condition index (PCI) which helps to implement an appropriate treatment. The aim of this study is to evaluate the condition of flexible pavement in Duhok city/Iraq urban network by PCI using visual pavement distress surveys. A representative network from flexible pavement of urban road network was considered. Overall, 22 roads covering all functional types with a total length of 65.64 km were selected. They include one principal arterial, one minor arterial, two major collectors, five minor collectors and thirteen local roads. Using Micro PAVER, 7.1 and ArcGIS software, the study results indicate that, based on PCI standard classifications values, 7% of road sections have a "Very poor" condition, 30% of road sections are in "Poor’’ condition, 32% of road sections have a "Fair" condition, 19% of road sections have a "Satisfactory" condition and 12% of road sections are in "Good" condition. Also, the principal and minor arterial roads had satisfactory condition with average PCI values of 70 and 75, respectively, whereas major and minor collector roads were in fair condition with lower average PCI values of 63 and 61. Local roads had the poorest condition with an average PCI of only 51. It was observed that the climate factor is the main cause of pavement deterioration in the urban network of Duhok city. The study findings will provide further guidance to pavement engineers when considering the maintenance schedules for existing pavements and predicting the future condition and lifespan of a road pavement in the selected urban network